ATTITUDE OF CLINICIANS TOWARDS CLINICAL DECISION-MAKING IN PROSTHODONTICS - Khan, Danish Azeem; Azad, Azad Ali; Aslam, Ayesha; Ishfaque, Qamar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the attitude of resident and consultant Prosthodontists towards clinical decision-making in complete denture prosthodonticsStudy Design: A cross-sectional study.Place and Duration of Study: Armed Forces Institute of Dentistry, Rawalpindi, from Nov 2019 to Jan 2020.Methodology: Fifty trainee and consultant prosthodontists from all over the country were included in the study. A questionnaire consisting of 10 questions aimed at assessing the approach towards clinical decision-making in complete denture prosthodontics was circulated among the study subjects using Google Forms. Data was analyzed using SPSS version 24.Results: Around 20 (40%) prosthodontists regarded patient’s personal values and preferences to be “very important” in clinical decision-making in contrast to their own values. Most of the clinicians 47 (94%) believed their patients were quite satisfied with them and around 31 (62%) prosthodontists believed that “choice of the best treatment results from negotiation between patients and clinicians after they have shared technical information as well as their values and preferences about the options”. No significant difference was observed in choice of response between males and females or between prosthodontists with varying clinical experience for any of the questions asked (p>0.05).Conclusion: Prosthodontists participating in the present study demonstrated a positive attitude towards shared decisionmaking in complete denture prosthodontics. No differences were observed between males and females in terms of attitude towards shared decision-making practices.